The Divided Government in Indonesia - Daniel Pasaribu (Universitas 17 Agustus 1945 Jakarta, 2023)
Since the fall of the authoritarian system, Indonesia completed the fundamental precondition to democratization through a series of constitutional amendments. As a young democratic country, Indonesia experienced a divided government for the first time under the administration of Joko Widodo. The Divided government is potentially believed to contribute to democratic breakdown. The objective of this research was to investigate how the divided government occurred and was resolved in Indonesia. The research used a qualitative methodology with a case study approach. The results showed that the divided government in Indonesia occurred because of the implementation of Indonesia’s political system adopting the combination of the presidential and multiparty systems. The divided government in Indonesia did not cause a deadlock or democratic breakdown as Joko Widodo resolved the problem by doing political maneuvers seeking political stabilization.